Electroencephalographic Correlates of Cognition among Nigerian Women with Epilepsy on Anti-epileptic Monotherapy - Ogunjimi LO; Alabi A; Osalusi B; Murtala A; Aderinola A; Ogunniyi A (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: The prospect of EEG as a potential biomarker for detecting a cognitive decline in those living with epilepsy has not been extensively studied. Objective: To determine the relationship between electroencephalographic (EEG) changes and cognitive functions in Women with Epilepsy (WWE). Methods: The study involved 100 adult WWE aged between 16 and 40 years on Levetiracetam (LEV) or Carbamazepine (CAB) monotherapy. Zung Self-Reporting Depression Scale (ZSRDS) was used to assess the mood of participants while the Community Screening Interview for Dementia (CSID) was used to assess various cognition domains. Results: The frequency of Periodic Epileptiform Discharges (PED) (p = 0.008), delta waves and theta waves (p = 0.004) were higher in WWE with Cognitive Impairment (CI) compared to those without CI. Lower cognitive scores were seen among those with delta wave across the domains of cognition with statistical significance for language fluency (p = 0.039), language comprehension (p = 0.000), and total CSID (p = 0.000). WWE with PED had a lower mean total CSID score compared to those without PED (p = 0.019). The absence of alpha wave (p = 0.027), presence of delta wave (p = 0.013), slow frequency (p = 0.015) and PED (p = 0.031) were EEG predictors of cognitive impairment. Medication type (p = 0.016) and depression (p = 0.001) were the clinical predictors of cognitive impairment in WWE. Conclusion: The frequencies of PED and slow waves were higher in WWE with CI while the absence of alpha wave, presence of delta wave and PED were EEG predictors of CI